Minyoo Matata – The Vicious Worm – A Taenia solium Computer-Based Health-Education Tool – in Swahili. Issue 10 (October 2017) - Trevisan, Chiara; Fèvre, Eric M.; Owiny, Maurice; Ngere, Isaac; Vang Johansen, Maria
Abstract : Lack of knowledge is one of the main risk factors for the spread of the zoonotic parasite Taenia solium. The computer-based health-education tool 'The Vicious Worm' was developed to create awareness and provide evidence-based health education as a specific measure in control strategies. To increase the reach of the tool, a new version in Swahili was developed and can now be downloaded for free fromhttp://theviciousworm.sites.ku.dk .